2015
DOI: 10.1186/s12936-015-0653-z
|View full text |Cite
|
Sign up to set email alerts
|

Early biting and insecticide resistance in the malaria vector Anopheles might compromise the effectiveness of vector control intervention in Southwestern Uganda

Abstract: BackgroundSouthwestern Uganda has high malaria heterogeneity despite moderate vector control and other interventions. Moreover, the early biting transmission and increased resistance to insecticides might compromise strategies relying on vector control. Consequently, monitoring of vector behaviour and insecticide efficacy is needed to assess the effectiveness of strategies aiming at malaria control. This eventually led to an entomological survey in two villages with high malaria prevalence in this region.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…This phenomenon is known as behavioural resistance and it is defined as any modification in insect behaviour that helps to circumvent the lethal effects of insecticides. Thus, through intraspecific behavioural shifts in biting time, location and host preference, malaria-transmitting mosquitoes avoid exposure to insecticides, feeding on humans when most people are not protected [129], jeopardising the current control strategy in Africa primarily based on indoor application of insecticides [130][131][132]. Recent studies conducted in West and East Africa have shown that indoor application of insecticides may induce intraspecific behavioural shifts towards early biting, exophagic biting and exophilic resting behaviour in malaria-transmitting mosquitoes [130,131,133].…”
Section: Behavioural Resistance To Insecticides Used In Public Healthmentioning
confidence: 99%
“…This phenomenon is known as behavioural resistance and it is defined as any modification in insect behaviour that helps to circumvent the lethal effects of insecticides. Thus, through intraspecific behavioural shifts in biting time, location and host preference, malaria-transmitting mosquitoes avoid exposure to insecticides, feeding on humans when most people are not protected [129], jeopardising the current control strategy in Africa primarily based on indoor application of insecticides [130][131][132]. Recent studies conducted in West and East Africa have shown that indoor application of insecticides may induce intraspecific behavioural shifts towards early biting, exophagic biting and exophilic resting behaviour in malaria-transmitting mosquitoes [130,131,133].…”
Section: Behavioural Resistance To Insecticides Used In Public Healthmentioning
confidence: 99%
“…This measure indicates the absolute difference in life expectancy between the regions with the lowest and highest Gross Domestic Product (GDP) per capita within each country. It was calculated as the population weighted linear regression slope of regional life expectancy and regional GDP per capita, with regional GDP scaled between 0 and 1 (22). Annual data on regional life expectancy and regional GDP per capita were obtained from the OECD for all Territorial Level 2 (TL2) regions within each country.…”
Section: Methods Setting Data Sources and Measuresmentioning
confidence: 99%
“…We measured the level of fiscal devolution in each country as the proportion of total government expenditure managed at a subnational level (state, region or local) obtained from the Organisation for Economic Co-operation and Development (OECD) fiscal decentralisation database (22). To measure regional health inequalities, we calculated the slope index of inequality (SII) of regional life expectancy for each country and each year.…”
Section: Setting Data Sources and Measuresmentioning
confidence: 99%
“…A recent study in the Cascades region in Burkina Faso showed high level of insecticide resistance (14) and that more than 50% of the major vectors, Anopheles gambiaes.l., were collected biting outdoor (15). These altered biting patterns -outdoor, early evening and morning biting habits-of Anopheles combined with resistance to insecticides showed that the mass distribution of insecticide treated nets alone eventually leads to a reduction in the e cacy of these interventions (16,17).…”
Section: Page 3/18mentioning
confidence: 99%